2008
DOI: 10.1177/1073191107311261
|View full text |Cite
|
Sign up to set email alerts
|

The Factor Structure of the Beck Depression Inventory–II

Abstract: The Beck Depression Inventory-II (BDI-II) is a frequently used scale for measuring depressive severity. BDI-II data (404 clinical; 695 nonclinical adults) were analyzed by means of confirmatory factor analysis to test whether the factor structure model with a somatic-affective and cognitive component of depression, formulated by Beck and colleagues, has a good fit. We also evaluated 10 alternative models. The fit of Beck's model was not good for all criteria. Three of the alternative models had a better fit in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
140
1
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(152 citation statements)
references
References 31 publications
6
140
1
1
Order By: Relevance
“…Results of recent studies using systematic confirmatory factor analyses (CFA) suggest that what is measured with the BDI-II is not a unidimensional construct (e.g., Vanheule et al 2008). On that basis, Vanheule et al (2008) recommend the use of three unidimensional subscales, which assess a somatic, an affective, and a cognitive dimension instead of one global score.…”
Section: Self-compassion Scale Short Form (Scs-sf)mentioning
confidence: 99%
“…Results of recent studies using systematic confirmatory factor analyses (CFA) suggest that what is measured with the BDI-II is not a unidimensional construct (e.g., Vanheule et al 2008). On that basis, Vanheule et al (2008) recommend the use of three unidimensional subscales, which assess a somatic, an affective, and a cognitive dimension instead of one global score.…”
Section: Self-compassion Scale Short Form (Scs-sf)mentioning
confidence: 99%
“…Nevertheless, some studies have suggested that the structure of BDI-II can be best described as three-dimensional, distributing the cognitive-affective dimension into two distinct factors. 17,20,41,56,66,98,122,136 Further analyses revealed that the BDI-II presents reasonable factorial invariance when assessing the severity of depressive symptoms; this covariance structure is equivalent across gender and ethnicity in American college students 58 and across gender in Taiwanese college students and adolescents. 60,61 Sophisticated alternative structural analysis of the BDI-II was strengthened by two investigative breakthroughs: the hierarchical model and the bifactor model.…”
Section: Content and Construct Validitymentioning
confidence: 99%
“…Although the bifactor model has been criticized, mainly because the orthogonality constraints among factors make interpreting the factors difficult (e.g. Vanheule, Desmet, Groenvynck, Rosseel, & Fontaine, 2008), there are several advantages of the bifactor model: it usually fits data better than competing models and it permits calculating measures of the degree of unidimensionality, and model-based indices of the reliability of general and subscale composite scores (Reise, 2012). Because of this, the bifactor model may be useful in assessing whether interpretation of total and/or subscale scores is possible.…”
mentioning
confidence: 99%